Considerations for Kansas State University’s College of Agriculture obtaining AAALAC accreditation - Bloomberg, Brooke (Kansas State University, 2010)
Kansas State University uses a variety of animals to fulfill the University’s research and teaching mission. K-State maintains a single Institutional Animal Care and Use Committee (IACUC) to oversee the use of all vertebrate animals used in research and teaching at K-State. K-State’s program is AAALAC accredited. The Association for the Assessment and Accreditation of Laboratory Animal Care, International (AAALAC) is a non-profit organization with the mission to promote the humane care of animals used in research and teaching. AAALAC is a private member association that evaluates and accredits member organizations by utilizing a peer review process. Accreditation signifies that an animal care and use program goes beyond meeting minimum standards required by law and strives for excellence to better meet the needs of the animals in their care. However, K-State’s accreditation is university-limited, meaning not all colleges that use animals for research and teaching are accredited. The College of Agriculture is not included in the accreditation even though it supports 15 animal facilities within the Department of Animal Science & Industry (AS&I) and 2 facilities located at Agricultural Experiment Stations (AES). Species housed in these facilities include; cattle, horses, swine, sheep, goats, and poultry. AAALAC reports that accreditation of agricultural animal programs lags behind other animal research and teaching programs. This may be due to multiple factors such as; minimal research funding sources require institutions to be accredited, minimal funding to make necessary facility upgrades, and a lack of conviction of how accreditation may benefit an agricultural animal program. This paper begins to discuss the scope of the program, identify common deficiencies, and provide suggestions for program improvement. As public pressure increases to improve care of animals in research and agricultural settings, it would benefit K-State to accredit all the institution’s animal facilities. The IACUC is a key player in this effort but support from K-State institutional leadership and the College of Agriculture is paramount. Those at K-State know the importance of the care we provide the animals in our facilities, but obtaining AAALAC accreditation will show our peers, supporting institutions, and our students that we strive for excellence in care of all our animals.
Keywords: Accreditation; Agricultural animal; Agriculture, Animal Culture and Nutrition (0475)